Between Tradition and Creation: Reinterpretations of Germanic Costumes in Fashion Design Education (Revista de Ensino em Artes, Moda e Design, 2026)
This work aimed to describe the process of creating, developing, and presenting reinterpretations based on the typical costumes used by Germanic folk groups in the Middle Itajaí Valley region, using the Project-Based Learning (PBL) methodology. The project was developed as part of the third phase of the Fashion Design course at UniSENAI - Centro Universitário Santa Catarina , Blumenau campus, and had four important stages: initially, the pieces were analyzed, and a historical study of the habits and customs of the inhabitants of the regions of origin of the studied pieces was carried out, followed by the creation of the reinterpretations; in the second stage, the creative process was carried out, where creativity techniques were applied under the supervision of the professors; after screening and refining the ideas, a sketch was chosen for prototyping; in the third stage, the pieces were modeled and made; and finally. In the fourth stage, the reinterpretations were presented in the form of a fashion show, made possible and managed by the organization of the TANZ event, a German folk dance festival, which took place in Pomerode/SC on July 25, 2024. The expected results of this study were to foster the expansion of students' ethnocultural repertoire, the appreciation and preservation of regional history, and to consolidate the link between academia and the cultural and artistic universe, which is so important in the creative repertoire of future designers. However, we can highlight the effective application of PBL in the teaching-learning process in higher education, since Project-Based Learning aims to establish a connection between practice and theory.
Keywords: active methodologies; product development; traditional german costumes; fashion design